Drawing a mobile system for meter reading through Bluetooth technology - Saravia Valle, Elizabeth (2013)
Currently in Peru, the water meter reading and electricity is conducted monthly by hand, resulting in loss of time to make a record twice: first in the manual page and then the billing system, additional human errors occur fingering, monthly billing with consequent inaccurate customer dissatisfaction. As an alternative solution arises designing a mobile system for remote meter reading, using Bluetooth technology.